The structural characteristics of progressive governments in Latin America - Gómez, Eduardo B. (2021)
Analyzing the social practice of the different progressive Latin American governements which were a response to the different social practices of neoliberalism, we can affirm that, taking into account the temporal and structural imbalances, the they were supported by a new type of extractivist there was an increasepolicy involving the installation of enclaves. At the same time ws increase price of primary products that were sold to the central States. Both elements, which implied the strong inflow of foreign currency, allowed the construction of a new type of State that I define as a Neo-commitment State which maintained a type of, unequal and combined dependency relationship with the central countries. Through it, the progressive governments could build a new multiclass domination pact between organized workers in the trade unión centrals and capital through which the different requests of workers and the various fractions of capital were channeled into a common project, in which of transnational capital were hegemonic. This allowed, in the same empirical calendar time, conditions for the accumulation of capital and for the improvement of woker’s living conditions. They promoted new focused social policies whose logic was onlyto give money to the marginal population mass so that it could go to the market and be able to goods. Thus they built up consumers and not citizenship, which implied a despoliticization.The maximalist objective of progressive governments was to build capitalism” with a human face”. This is how they shaped their social and political legitimacy.